Personal Counselling at an Ontario Community College: Client Groups, Service Usage, and Retention - Porter, Shirley (Canadian Journal of Counselling and Psychotherapy, 2011)
This study focused on personal counselling clients in a community college in Ontario. Using archival records from the 2008–2009 academic year, at-risk client groups were identified and compared with respect to usage rates and retention. Significant differences were identified. Overall, first-year students who engaged in personal counselling had a 7.6% higher retention rate than that of the first-year student population as a whole. Students with confirmed disabilities (CD) and probable disabilities (PD) attended significantly more personal counselling appointments than students with no reported disabilities (ND). CD clients had a 15% higher retention rate than that of PD clients.